A Rural Interprofessional Educational Initiative: What Success Looks Like - Deirdre Jackman; Olive Yonge; Florence Myrick; Fred Janke; Jill Konkin (Rural Nurse Organization; Binghamton University, 2016)
The researchers implemented an interprofessional education (IPE) pilot program, wherein Final Year baccalaureate nursing students and 3rd Year medical students undertook preceptorships concurrently in a semi-rural acute care setting. The goal was to emphasize interprofessional (IP) collaboration and team-building. The researchers sought to determine how hands-on, clinically-based IP experiences could improve classroom-based IPE, and how the rural context might mediate such experiences. This article is an exploration of how participants defined a successful rural IPE experience, and which factors promoted or hindered that success. The definition of rural as used in the context of the research is to live outside of a major city. Three nursing and four medical students who agreed to undertake rural preceptorships were recruited through their supervising faculty. Upon their placement, three registered nurses and four physicians, assigned to precept the students, also agreed to take part. The researchers collected data through midpoint and endpoint semi-structured interviews, and two focus groups. The data were coded and analysed using Glaserian grounded theory. In the participants' view, successful rural IPE resulted in enhanced knowledge of each others' scope of practice, firsthand insights into rural IP teamwork and increased confidence in working with other disciplines. Authenticity was a key distinguishing rural feature. Success moreover depended on buy-in and facilitation by preceptors and staff, and student initiative and self-reliance. Hinderances to success were lack of logistical support, professional inertia or turf-consciousness, and student discomfort with IP engagement. Over the course of the pilot, the students grew to emulate their rural preceptors' interprofessional collegiality beyond the clinical setting. The results of this study support the implementation of IPE in clinical rotations as an alternative or an adjunct to classroom-based IPE. The rural context may be particularly advantageous to clinical IPE owing to comprehensive coverage of acute care and holistic, community focus. Keywords: interprofessional education, medical students, nursing students, preceptorship, semi-rural, Western Canada DOI:  http://dx.doi.org/10.14574/ojrnhc.v16i2.417